PENGEMBANGAN BAHAN AJAR MATEMATIKA BERINTEGRASI AL-QUR’AN DAN AL-HADIST MATERI PECAHAN KELAS VII DI SMP - Arinamilati, Atik; Hartoyo, Agung; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTo execute the learning of KI-1 and KI-2, this research is conducted to develop mathematic’s learning materials with the integration of Qur'an and Al-Hadith. The quality of the ingredients is tested based on three criteria, namely validity, effectiveness, and practicality. To find out its effectiveness and practicality, a limited trial was carried out on 21 students of class VII at SMPIT Al-Mumtaz Pontianak. The ADDIE model used in developing teaching materials includes 3 stages, namely analysis, design, and development. Data collection tools include validity questionnaire, post-test, and practicality questionnaire. The validity questionnaire was filled by material experts and media experts. Study test results completed by students. Practicality is filled by the teacher and students. The results of the study included an average score of validity of 4.26 in the